Enhancing End-Of-Life Care For Older Adults: The Critical Role Of Nursing (The Review of Diabetic Studies, 2025)
Background: The aging global population has increased the demand for high-quality end-of-life (EOL) care. Nurses play a foundational role in ensuring comfort, dignity, and autonomy for older adults experiencing complex, life-limiting conditions.Methods: A narrative synthesis of current literature was reviewed, focusing on nursing roles, competencies, challenges, and best practices in geriatric EOL care. Key themes included symptom management, interdisciplinary collaboration, communication, advance care planning, and cultural competence.Results: Findings highlight nurses’ central involvement in holistic assessment, pain and symptom management, decision-making support, and family education. Nurse-led coordination improves continuity of care, reduces unnecessary hospitalizations, and enhances satisfaction among patients and caregivers. Barriers such as staffing shortages, communication gaps, legal uncertainties, and emotional burden negatively impact care quality. Facilitators including targeted education, institutional support, and telehealth innovations strengthen nursing capacity and patient outcomes.Conclusions: Nurses are essential to deliver comprehensive EOL care for geriatric populations. Enhancing training, resources, and supportive policies can mitigate existing challenges and elevate the standard of care, ensuring older adults receive compassionate, person-centered support at the end of life.